Blank Faces - Meghanne Barker (Semiotic Review)
The purpose of this thematic issue is to explore other means and results of making faces blank. We first explored these questions with a panel on the semiotics of “Blank Faces” at the 2016 Annual Meetings of the American Anthropological Association (AAA), in Minneapolis, Minnesota, which included contributions from Silvio, Nozawa, and others. In exploring the blank face, we aim to illuminate the expectations that people have for their own faces or the ones they meet, even if those expectations so frequently fall short of the demands placed on them. This thematic issue includes original research articles on topics such as the editing of portraits for match-making purposes (Alpert), the range of human capacities to recognize and remember faces (Pearl), the alignment of human faces with characterological types (Occhi), and the proliferation of a face in urban landscapes to the effect that she is seemingly ubiquitous, and yet never meeting the viewer’s gaze (Manning). As such, this issue is concerned with the relationship between the face as a locus of interaction in everyday life and the face as an image that lends itself to typification, along with the layered processes of semiosis and the social relationships produced through encounters with faces.